Effect of Heterogeneity and Innovation on Decision Making – “A study of a telecom service provider in UAE" - Kumar, Ashwin Ajith (2016)
In this thesis, the effect of heterogeneity and its impact on innovation market in UAE is explored. As market mature across the globe, every telecom operator has to increase their value and reduce their commercial costs. The only way to do this is by rethinking their approaches and to develop new ways in order to keep their customers satisfied. Furthermore, different aspects of diversity that service providers should take care of is discussed. Starting with national culture where it is divided into four different categories. These include Hofstede’s four cultural dimensions, Power distance index (PDI), Uncertainty avoidance index (UAI) and Individualism. The second diversity factor that must be taken into account is the age difference that exists between the customers of the service providers. The third factor that is discussed is the gender composition. The gender compositions also has an impact on what a customer wants from the service provider. For instant business customers want business related services. Some of the female customers would like to have more services related to fashion or makeup. Every customer has different choices and the service provider must make sure that its customer is properly supplied with the services that he/she wants on a daily basis with the minimum cost so that he/she can purchase it without facing financial problems. The fourth factor that has an impact on the service provider is innovation. Based on each factors that have been discussed, it is the job of the service provider to categorize its customers based on factors such as age, gender and culture. Unless proper categorization is not done, there will be no proper room for service innovation. Furthermore, the different generations of innovations are described which are: first generation innovation, second generation innovation, third generation innovation, fourth generation innovation and the last one which is fifth generation innovation. After a brief description of the different impacts of customer diversity, then the research objective which is firstly how decision making plays a critical role in projects along with its different challenges is analyzed. Secondly, to investigate how diversity can enhance or hinder decision making is discussed followed by how diversity influences different innovation ideas that the service provider can provide is investigated. The section after this shows the change in the 3 MS Project Management ID NO: 2014203093 consumption of sms, phone calls and internet services that have increased. This is done by using graph from the telecommunication sector provider. Some of the possible reasons behind the increase in the subscription is also analyzed and evaluated. Three types of analysis methods have been used which are based on demographic profile, reliability and gap analysis have been made. Furthermore, in the end new ways of encouraging people to use the services have been discussed which can benefit the service provider if they are followed. Analysis was conducted not only on the diverse workforce that worked for the organization but also on the customers. Through the analysis, it was found that based on the questionnaire response of 33 people, how long the people have been working for the organization. By making use of a pie chart, the number of people working in the firm from 5 years to above 21 years was determined. Furthermore, how effective each of these members were also taken into account by how many projects they have started. After that, how they were able to motivate each other based on their team work was also determined along with ways project manager resorts to different styles rather than the only means of approach in order to tackle an obstacle. Furthermore, proper analysis of the tactics that the project manager adopted was taken into account. Based on this survey that was conducted, one could determine if the employees did learn anything new or not. The last survey in the employee section that was conducted shows the project complexity that the employees were working on. It was then followed by surveys based on the customer’s background and reliable the test was in order to take into consideration. Furthermore, different ways of approach that the organization could use in order to boost their innovation ideas was also taken into consideration. Some of these included new digital channels, mobile commerce, low-cost channels, direct mixed points of sale, free lancers and street sales. In the conclusion section, the importance of diversity workforce is highlighted followed by the advantage an organization can have if their workforce is put under a capable leadership. Not only will they provide different solutions from which the leader can choose from but they will also provide innovative ideas which the leader can take into account and develop new products to satisfy their customers. 4 MS Project Management ID NO: 2014203093 In the last part of the thesis, some recommendations are provided such as more focus should be placed in the development of leadership, how employees should be rewarded for their ideas to encourage them more etc.